Modern trends in the legal regulation of the use of educational technology in the educational systems - P G Gribov (RUDN Journal of Law, 2014)
This article is devoted to disclosure of some aspects of modern education. The analysis of educational systems and technologies is carried out, sources and tendencies are opened. The special attention is paid to studying of the main lines of the student using these technologies and also social aspects in general are considered. In the conclusion, we will note that the successful project in the sphere of educational technologies can turn out when solves not only the main objective. Similar systems can be used, including, for collective discussion on application of acts. A characteristic example is the bank environment where in the sphere of the currency legislation, there are regular changes, especially when there are comments or letters from the Central Bank of Russia. Similar systems can inform in due time workers on changes and organize collective discussion of innovations, thereby increasing overall performance.